Resonant properties of the metal dielectric plate in a waveguide - Арсеничев, С.А.; Полетаев, Д.А.; Слипченко, Н.И.; Старостенко, В.В.; Таран, Е.П.; Шадрин, А.А. (Radiotekhnika, 2012)
The cycle of experimental and theoretical researches in the properties of the metal dielectric plate in the waveguide is carried out. The action of the plate size and its place in the waveguide section on the resonant properties is clarified. A sufficiently good correlation between the experimental data and the numeral calculations is obtained.